Clemente Riedemann. Riedemann Blues. (Valdivia: Ediciones Kultrún, 2017, 80 páginas). - Pino Ojeda, Walescka (Árboles y Rizomas, 2019)
Book Review. Clemente Riedemann. Riedemann Blues. (Valdivia: Ediciones Kultrún, 2017, 80 páginas).